Deriving Specifications of Control Programs for Cyber Physical Systems. (30th April 2019) - Burns, Alan; Hayes, Ian J; Jones, Cliff B
Abstract: Cyber physical systems (CPS) exist in a physical environment and comprise both physical components and a control program. Physical components are inherently liable to failure and yet an overall CPS is required to operate safely, reliably and cost effectively. This paper proposes a framework for deriving the specification of the software control component of a CPS from an understanding of the behaviour required of the overall system in its physical environment. The two key elements of this framework are (i) an extension to the use of rely/guarantee conditions to allow specifications to be obtained systematically from requirements (as expressed in terms of the required behaviour in the environment) and nested assumptions (about the physical components of the CPS); and (ii) the use of time bands to record the temporal properties required of the CPS at a number of different granularities. The key contribution is in combining these ideas; using time bands overcomes a significant drawback in earlier work. The paper also addresses the means by which the reliability of a CPS can be addressed by challenging each rely condition in the derived specification and, where appropriate, improve robustness and/or define weaker guarantees that can be delivered with respect to the corresponding weaker rely conditions.